2018
DOI: 10.3389/fnbeh.2018.00006
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress-Related Elevations in Reaction Time Variability Are Associated with Brain Volume Reductions in HIV+ Adults

Abstract: There is burgeoning evidence that, among HIV+ adults, exposure to high levels of early life stress (ELS) is associated with increased cognitive impairment as well as brain volume abnormalities and elevated neuropsychiatric symptoms. Currently, we have a limited understanding of the degree to which cognitive difficulties observed in HIV+ High-ELS samples reflect underlying neural abnormalities rather than increases in neuropsychiatric symptoms. Here, we utilized a behavioral marker of cognitive function, reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…The average age for fourteen of fifteen studies, (one study reported the age range only) was 40 years. Eight were all-female studies (Malan-Muller et al, 2013 ; Rubin et al, 2017 , 2015 , 2016 ; Spies et al, 2016 , 2012 ; Spies, Fennema-Notestine, Cherner, & Seedat, 2017 ; Womersley, Spies, Seedat, & Hemmings, 2019 ) and two were all-male studies (Deiss et al, 2019 ; Pukay-Martin, Cristiani, Saveanu, & Bornstein, 2003 ), with the remainder (five studies) including both men and women (Clark, Arce Renteria, Hegde, & Morgello, 2018 ; Clark et al, 2012 ; Kapetanovic et al, 2020 ; Lin et al, 2011 ; Watson et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average age for fourteen of fifteen studies, (one study reported the age range only) was 40 years. Eight were all-female studies (Malan-Muller et al, 2013 ; Rubin et al, 2017 , 2015 , 2016 ; Spies et al, 2016 , 2012 ; Spies, Fennema-Notestine, Cherner, & Seedat, 2017 ; Womersley, Spies, Seedat, & Hemmings, 2019 ) and two were all-male studies (Deiss et al, 2019 ; Pukay-Martin, Cristiani, Saveanu, & Bornstein, 2003 ), with the remainder (five studies) including both men and women (Clark, Arce Renteria, Hegde, & Morgello, 2018 ; Clark et al, 2012 ; Kapetanovic et al, 2020 ; Lin et al, 2011 ; Watson et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were ten case-control studies (Clark et al, 2012 ; Kapetanovic et al, 2020 ; Malan-Muller et al, 2013 ; Pukay-Martin et al, 2003 ; Rubin et al, 2017 , 2015 ; Spies et al, 2016 , 2012 , 2017 ; Watson et al, 2019 ) and five cross-sectional studies (Clark et al, 2018 ; Deiss et al, 2019 ; Lin et al, 2011 ; Rubin et al, 2016 ; Womersley et al, 2019 ). Eight studies were longitudinal in design (Malan-Muller et al, 2013 ; Rubin et al, 2017 , 2015 , 2016 ; Spies et al, 2016 , 2012 , 2017 ; Womersley et al, 2019 ) but only one of these presented longitudinal data examining the relationship between childhood trauma and HIV and change in cognition over time (Spies et al, 2017 ) and one examined the relationship between perceived stress and PTSD and NCI over time (Rubin et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesised that carriers of the ApoE ε4 isoform would perform worse on cognitive tests, and that these deficits would be further accentuated by a history of CT. Studies have associated ApoE ε4 genotype with a range of cognitive effects in HIV including executive function, perceptual speed, verbal fluency, learning, memory and global cognitive function (Andres et al 2011;Chang et al 2011;Hoare et al 2013;Panos et al 2013;Mukerji et al 2016;Wendelken et al 2016). The interaction of CT and HIV has also been associated with a variety of cognitive impairments including diminished attention/working memory, executive function, language, motor skill and processing speed (Spies et al 2016(Spies et al , 2017Clark et al 2018). Based on the broad spectrum of possible impairment, we thus decided to examine both global cognitive function as well as cognitive domains in our study.…”
Section: Introductionmentioning
confidence: 99%